Pengaruh Aspek Arsitektur dan Perencanaan Kota Terhadap Terbentuknya Ikatan Batin Dengan Suatu Tempat (Place Attachment) - Ernawati, Jenny (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2014)
This paper reports an empirical study that was aimed to explore community’s evaluations of architecture and urban planning qualities and it’s influence on place attachment. Place attachment is understood as emotional or affective connection that people develop with their places of residence, due to the meaning given to that site. This study used a survey research design which was conducted in two stages. The first stage of the surveys was to explore variables of architecture and town planning qualities using a combination of open-and-close-ended questions. Forty respondents selected randomly to participate in this phase of study. This resulted 28 variables of architecture and urban planning qualities, which were then used for the next stage of the survey. The second stage of the survey used questionnaire involving seven-point Likert scale to evaluate those qualities and unidimensional scale of place attachment consisted of five variables. There were 193 respondents from five different neighbourhoods in Malang chosen randomly to participate in the survey. Several multivariate data analysis, including factor analysis and regression analysis were used to explore effects of architecture and urban planning qualities on place attachment. Results indicated that, in general, perceived architecture and urban planning qualities are significant as predictors of place attachment. These predictors consist of four factors that are Built Environmental Aesthetics; Pedestrian Facilities; Street Network; and Green Open Space Availability. Those four factors influence 27.2% of the development of place attachment.Keywords: place attachment; community’s evaluations; architecture; urban planning and design